An analysis of the various factors affecting demand that leads to the proliferation of Jollibee food chains in Iloilo City - Arroyo, Camille Kate Y.; Calderon, Patricia August J.; Juntado, Lestle M.; Yong, Marie karen Q. (2003.)
This study was conducted to identify the various factors that affect customer's preferences for Jollibee Food Chains in Iloilo City. Entitled " An analyis of the various Factors Affecting Demand that Leads to the Proliferation of Jollibee Food Chains in Iloilo City," it specifically aimed to determine the frequency of dining at Jollibee Fastfood joints by Ilonggos, and if indeed, Jollibee is the most preferred fastfood chains in the city. It also strives to analyze the significance of various factors affecting demand such as company name/image, product quality, price, location, operations, facilities and marketing strategies. In accordance with the objectives, questionnaires were distributed wherein the researchers focused on fifteen (15) randomly selected respondents from each of the nine (9) Jollibee branches in Iloilo City. The results of the analysis showed that Jollibee was indeeed unanimously chosen as the most preferred fastfood chain in Iloilo City while McDonald's and Kentucky Fried Chicken ranked second and third, respectively. Among the factor identified, brandname recognition was the primary factor that affected customer's patronage along with good advertising, taste, product freshness, quality and price, promotional gimmicks, proper ventilation and lighting, cleanliness and accessibility. Ilonggo diners frequent Jollibee food branches at an average of one to two times a week.
Research Paper (BA 200 - Business Research). -- Iloilo City : University of the Philippines in the Visayas-College of Management, March 21, 2003.